Correlation study in problem solving ability and reading comprehension ability among sophomore students in San Juan Municipal High School - Dellosa, Concepcion D. (Manila : National University, 1998)
The results of this study will benefit the society as a whole. It also serves as a guide to improve their Mathematics and English programs such that the structures of both subjects may be adapted to the students' level of comprehension.
Title page -- Approval Sheet -- Acknowledgement -- Dedication -- Table of contents -- List of tables -- List of figures -- Chapter 1. The Problem and its setting -- Chapter 2. Review of related literature and studies -- Chapter 3. Methods and Procedure -- Chapter 4. Presentation, Analysis, and Interpretation of Data -- Chapter 5. Summary, Conclusion, and Recommendation -- Bibliography -- Appendices.
Research Method : Descriptive Method.
Includes bibliographical references.